Flap design and perfusion are keys of success: Axial fasciocutaneous posterior thigh flaps for deep small pelvic defect reconstruction - Kehrer, Andreas; Lamby, Philipp; Miranda, Benjamin H.; Prantl, Lukas; Dolderer, Juergen H. (Clinical hemorheology and microcirculation, 2016)
BACKGROUND AND OBJECTIVES: Radical excisions of the rectum often result in large perineal and intrapelvic defects. Compromised wound healing can delay adjuvant therapies and limit the patient's prognosis. With current treatment, integrity of the abdominal wall may be maintained. The defect geometry is unique and requires extensive volume for reconstruction. This study describes the surgical technique and reports clinical outcomes of fasciocutaneous posterior thigh flaps as preliminary data for this indication. METHODS: Thirteen posterior thigh flaps were used in eleven patients between 2013-2015. Patients were prospectively followed-up for the pursposes of this case series. Flap dimensions and volume were measured in two representative cases. The surgical technique is described in detail. RESULTS: Dead space occlusion was achieved in 100 of cases. No intestinal herniation was detected. Vaginal wall defects were concurrently reconstructed in two patients. Total flap volume was calculated as 315-360 cm3. The fasciocutaneous flaps were easy to harvest, versatile to manipulate and did not result in significant function deficits. CONCLUSIONS: In contrast to classic Vertical Rectus Abdominis Muscle (VRAM) flaps, the posterior thigh flaps preserve abdominal wall function and should be considered as a reliable alternative option in reconstruction of intrapelvic defects including neighboring organs. Future studies of larger patient series should be executed to verify our findings and determine the optimal point in time for reconstruction.
CRIS-Team Scopus Importer:2024-12-11
Keywords: pelvic defect; perineal defect; posterior thigh flap; rectum extirpation; Rectum resection; VRAM flap